Battery Efficiency of Mobile Devices through Computational Offloading: A Review - Ali, Mushtaq; Jasni, Mohamad Zain; Mohamad Fadli, Zolkipli; Gran, Badshah (IEEE, 2015)
Smart Internet Devices (SIDs) particularly Smartphones are soon turned to be super computers, while the restricted battery timing is a focused issue which hinders the steady meeting expectations yield of these devices. In addition, various sensors, high resolution LCDs, wireless interfaces, GPS and other advanced features drain battery quickly, thus, shrinking the operational time. Subsequently, increasing battery life of SIDs has happened to dire investigation significance at hardware and programming levels, both alike. The intention of our work is to evaluate computational offloading; sending power-intensive processing to remote servers in cloud and accepting the outcome back on device’s screen. Furthermore, this paper gives a review of previous research work on computational offloading. We then summarize distinct research work with their respective findings and limitations. In addition, a short critical analysis of the review works following the summarized data.